Practical experiences with a syrup feeding study design based on a new MRL guideline SANTE11956/2016 rev.9 (2018) - Cohen, Yotam; Berger, Christian; Gonsior, Gundula; Knäbe, Silvio (Julius-Kühn-Archiv, 2020)
A new study design, according to the guideline SANTE11956/2016 rev:9 (2018), was established to determine the maximum residue level (MRL) of plant protection products in honey. The guideline describes a syrup bee feeding study designed as a worst-case scenario for transferring plant protection products into honey. Previously, field and semi-field studies designs were used. The objectives of this study were to validate the suitability of this feeding semi-field studies according to the new guideline.